Studying the shielding of an electromagnetic field by a textile material containing ferromagnetic nanostructures - Glyva, V.; Barabash, O.; Kasatkina, N.; Katsman, M.; Levchenko, L.; Tykhenko, O.; Nikolaiev, K.; Panova, O.; Khalmuradov, B.; Khodakovskyy, O. (Eastern-European Journal of Enterprise Technologies, 2020)
1. It has been established that the most efficient method to ensure the sticking together between ferromagnetic nanoparticles and a textile material is to apply a magnetic liquid to the material and to expose it to a heterogeneous permanent magnetic field. Our study has proven that under the influence of a magnetic field with an intensity of 450 A/m for 12 hours the implantation of nano-particles into the fibers of a linen fabric becomes practically irreversible. 2. The study has shown that when impregnating a textile material with a magnetic liquid in the amount of 45–50 g/m2 (the content of nanoparticles is 9 % by weight) the shielding coefficients for 1–3 layers of the material are: for an electric field of industrial frequency, 1.4÷3.8; for a magnetic field, 1.9÷8.1. Following the magnetic treatment of the material, these indicators are 2.9÷8.6 and 2.3÷8.9, respectively. At the same time, the magnetically-treated material was treated with a synthetic detergent. Fig. 2. The distribution of a magnetic field В/В0 in the human body (in the middle plane) exposed to the longitudinal magnetic field В0 and in the presence of protective clothing: a, b, c ‒ the presence of 1, 2, 3 layers of protective fabric Ecology 31 3. It has been etermined that in order to remove the technological liquids (grease, oleic acid), which are the mandatory ingredients of a magnetic liquid, it would suffice to use synthetic etergents. In this case, the degree of washing out the ferromagnetic particles is acceptable. The use of the ethyl alcohol-based fluid, with the subsequent neutralization of oleic acid by an alkaline solution, turned out to be impractical because of the washout or chemical destruction of the nano-particles by alkali, which was confirmed experimentally. 4. In order to determine the possibility of manufacturing special clothing from the designed material aimed to protect against electrical and magnetic fields, we simulated the magnetic field distribution in the human body using a finite element method and the Comsol oftware. It was established that, notwithstanding the acceptable, in general, results, the cervical spine of the human body experiences the increased field intensity due to the magnetic flux compression. This should be taken
Изучение экранирования электромагнитного поля текстильным материалом, содержащим ферромагнитные наноструктуры
DOI: https://doi.org/10.15587/1729-4061.2020.195232. Посилання на анотацію: http://journals.uran.ua/eejet/article/view/195232 Послання на статтю на укр. мові: http://journals.uran.ua/eejet/article/download/195232/201894 UDC 537.87:669.162.12 (045) ISSN 1729-3774 Scopus
Keywords: електромагнітне поле; наночастинки; текстильний матеріал; коефіцієнт екранування; магнітна обробка; 537.87:677.07